2022
DOI: 10.3390/s22030718
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric and Electrochemical Screening for Early Detection of Diabetes Mellitus and Diabetic Retinopathy—Application of Sensor Arrays and Machine Learning

Abstract: In this review, a selection of works on the sensing of biomarkers related to diabetes mellitus (DM) and diabetic retinopathy (DR) are presented, with the scope of helping and encouraging researchers to design sensor-array machine-learning (ML)-supported devices for robust, fast, and cost-effective early detection of these devastating diseases. First, we highlight the social relevance of developing systematic screening programs for such diseases and how sensor-arrays and ML approaches could ease their early dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 150 publications
(220 reference statements)
0
6
0
3
Order By: Relevance
“…Similar to sweat, the physicochemical properties and enrichment of tears can be detected non‐invasively with colorimetric biosensors to determine the health status of the living body 95–97 . Contact lenses combined with colorimetric sensors have been widely used for in situ monitoring of tears.…”
Section: Colorimetric and Fluorescence Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to sweat, the physicochemical properties and enrichment of tears can be detected non‐invasively with colorimetric biosensors to determine the health status of the living body 95–97 . Contact lenses combined with colorimetric sensors have been widely used for in situ monitoring of tears.…”
Section: Colorimetric and Fluorescence Biosensingmentioning
confidence: 99%
“…Similar to sweat, the physicochemical properties and enrichment of tears can be detected non-invasively with colorimetric biosensors to determine the health status of the living body. [95][96][97] Contact lenses combined with colorimetric sensors have been widely used for in situ monitoring of tears. Riaz et al employed Anthocyanin pigments to functionalize the polymeric matrices of contact lenses to continuously monitor the ocular pH values.…”
Section: Tears Detectionmentioning
confidence: 99%
“…2. In this example, the kernel k[n] = [1], [2], [3], [4] [8], [8], [9], [14], [19], [20]. The provided example demonstrates that the correlation will reach its maximum value when the input signal most closely resembles the values of the kernel.…”
Section: A Proposed Correlation Operationmentioning
confidence: 99%
“…According to medical studies, small amounts of glucose are found in saliva, tears, sweat and urine [3]. These biological samples offer the potential for non-invasive glucose level prediction in the body.…”
Section: Introductionmentioning
confidence: 99%
“…Some outstanding research has been successfully applied in breast cancer 6 , hepatocellular carcinoma 7 , lung cancer 8 , and other cancer types automatic recognition and survival prediction tasks 6 8 . Similar to cancer research, many machine learning methods have been proposed for the effective diagnosis, prognosis, management, and treatment of diabetes 9 11 in the past few years. For the diagnosis and treatment of diseases, the methods used by researchers are divided into rule-based methods 12 – 15 , such as C4.5, CART, and random forest (RF), and nonrule-based methods 16 19 , such as support vector machine (SVM), Bayes, k-nearest neighbor (k-NN), and neural network (NN).…”
Section: Introductionmentioning
confidence: 99%